Facile fabrication of diatomite‐based sponge with high biocompatibility and rapid hemostasis. Issue 46 (6th July 2021) - Yang, He; Ma, Zhifang; Guan, Xinghua; Xiang, Zehong; Ke, Yue; Xia, Yu; Xin, Zhirong; Shi, Qiang; Yin, Jinghua
Abstract: Excessive bleeding causes a large part of deaths in wars and accidents. It is necessary to prepare a hemostatic material with excellent performance and low cost through a facile strategy. Herein, the diatomite is modified with (3‐Aminopropyl) triethoxysilane (APTES) to endow the aminated diatomite (ADia) with positive charge and interface compatibility with chitosan (CS) and sodium alginate (SA). Then, the facile fabrication of CS/SA/ADia sponge is successfully obtained by cross‐linking with calcium ions. Compared to CS/SA sponge, the introduction of ADia further enhances the mechanical properties and hemostatic performance of CS/SA‐based sponges. The composite sponges with 30 wt% ADia are demonstrated to possess high biocompatibility, compressive strength, water adsorption, and rapid hemostatic capability both in vitro and in vivo. The hemostatic performance is interpreted by activation of coagulation factors and platelets in intrinsic pathway, promotion of blood cell adhesion and formation of fibrin network. Our work provides an effective strategy to develop rapid hemostatic materials with low cost and high efficiency. Abstract :